The Influence of Profitability, Capital Structure and Intellectual Capital on Company Value with Good Corporate Governance as Moderation (Case Study on Construction Sector Companies Listed on the IDX in 2019-2023) - Puteri Sarah Mutia; Winwin Yadiati; Evita Puspitasari (Green Publisher Indonesia, 2025)
Abstract: This study analyzes the influence of profitability, capital structure, and intellectual capital on company value with Good Corporate Governance (GCG) as a moderation variable, especially in construction sector companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The method used is regression analysis with the Fixed Effect Model approach. The results show that profitability has a positive but insignificant effect on the company's value, while capital structure has a negative and significant effect. Intellectual capital shows a positive but not significant influence, and GCG cannot moderate the influence of profitability on a company's value but can weaken the negative impact of capital structure. These findings emphasize the importance of debt management and effective GCG implementation to increase the value of companies in the construction sector.